2019
DOI: 10.1016/j.parkreldis.2019.01.019
|View full text |Cite
|
Sign up to set email alerts
|

General and abdominal adiposity and the risk of Parkinson's disease: A prospective cohort study

Abstract: Introduction: Due to demographic change, an increase in the frequency of Parkinson's disease (PD) patients is expected in the future and, thus, the identification of modifiable risk factors is urgently needed. We aimed to examine the associations of body mass index (BMI) and waist circumference (WC) with incident PD. Methods: In 13 of the 23 centers of the European Prospective Investigation into Cancer and Nutrition (EPIC) study, a total of 734 incident cases of PD were identified between 1992 and 2012 with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The amount of smoking played a subtle role in the development (135). Another study that examined body mass index and waist circumference of PD patients found a possible interaction between anthropometry, sex, and smoking and PD risk (136). Similarly, new prodromal markers are expected to be found when large-scale statistical analyses of patient lifestyle factors are completed.…”
Section: Other Prodromal Markersmentioning
confidence: 99%
“…The amount of smoking played a subtle role in the development (135). Another study that examined body mass index and waist circumference of PD patients found a possible interaction between anthropometry, sex, and smoking and PD risk (136). Similarly, new prodromal markers are expected to be found when large-scale statistical analyses of patient lifestyle factors are completed.…”
Section: Other Prodromal Markersmentioning
confidence: 99%
“…According to the study by Pak et al, weight loss is linked to rapid striatal dopaminergic degeneration in PD (Pak et al, 2018). Additionally, it is reported that worse disease severity is associated with lower BMI (Riso et al, 2019; Umehara et al, 2017; van der Marck et al, 2012) and high BMI can slow disease progression (Umehara et al, 2017); on the other hand, rare studies reject the idea indicating the association of BMI (Guimarães et al, 2012) and weight loss (Bernhardt et al, 2016) with disease severity.…”
Section: Weight Gain/loss and Parkinson's Diseasementioning
confidence: 99%
“…In addition to the observed weight and BMI changes in PD patients, researchers have presented the effects of different patterns of BMI and body weight conditions on the risk for developing PD. Some studies reported that both low and high BMI can pose a risk for PD (Sharma & Lewis, 2017); however, a cohort study on 734 cases, chosen incidentally from 13 of the 23 centres of the of PD, who were identified between 1992 and 2012, with a mean follow‐up of 12 years, has reported no association between BMI and PD risk (Riso et al, 2019). Researchers explain weight gain as a risk factor of PD according to its impact on metabolism including reactive oxygen species (ROS) production, insulin resistance and inflammation, which could contribute to PD pathogenesis (Kim et al, 2020).…”
Section: Weight Gain/loss and Parkinson's Diseasementioning
confidence: 99%
“…In light of abdominal obesity, Chen et al prospectively examined two large cohorts of men and women in the United States (US), and concluded that a greater waist circumference (WC) was associated with future development of PD among never smokers 20 . Although another US-based cohort study showed null association between WC and PD risk, a European multi-center cohort study in 2019 revealed that female smokers had a 64% increase in the risk of PD development per 10 cm increase in WC 16 , 19 . Investigations on the association between central adiposity and PD risk have provided a closer look on the mechanism of PD through the perspective of the effect of adiposity-related inflammation on neurodegeneration.…”
Section: Introductionmentioning
confidence: 96%
“…The deleterious effect of general obesity (measured by body mass index [BMI]) on PD risk has been demonstrated in several epidemiologic studies; 9 – 11 however, other studies reported opposite results or even null associations 12 18 . Moreover, studies using anthropometric parameters other than BMI are relatively limited 16 , 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%